ANALYSIS OF DEPOSITION PHENOMENA AND RESIDUAL-STRESS IN PLASMA SPRAY COATINGS - LEE, JD; RA, HY; HONG, KT; HUR, SK (ELSEVIER SCIENCE SA LAUSANNE, 1992)
An analytical model was developed to describe the deposition process. Assuming the plane solid-liquid interface to move with the solidification rate calculated by this deposition model, the thermal history was also calculated by a finite difference method. The solidification rate changes periodically, causing a temperature fluctuation in the coating layer and substrate during deposition. As the liquid remains discontinuously at the coating surface, interlamellar layers, such as oxide or glass layers, form discontinuously. These phenomena can be confirmed in the Ni17Cr4Si3B deposit. Using the stress model proposed in this study, the stress distribution within the ZrO2 coating and iron substrate was derived from the thermal history by a finite element method. The shape of the predicted residual stress distribution was in good agreement with that measured by X-ray diffraction in the PSZ coating. The differences between the theoretical predictions and experimental results are discussed.
Keywords: PARAMETERS; DROPLETS